FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN K4 DALAM PELAYANAN ANTENATAL DI KELURAHAN RAWANG BARAT PADANG - Hasni Mastian (Faculty of Public Health, Andalas University, 2009)
Aternal, mortality rate in Indonesia was 470 per 100.000 life birth in 2004. Public Health Centre (PHC) Rawang Barat is the only one of all PHC in Padang City that has under target reached of the fourth examination of pregnancy with 77,2%. One intervention to decrease the maternal mortality is to have antenatal care at least once in first and second trimester and twice in third trimester during of any pregnancy's period. This research is to get some factors related to the fourth antenatal care of pregnancy. The research design is across sectional study, done at Rawang Barat in September 2008 up to April 2009. Population in this research are all mothers with 0-6 months of baby with amount 67 babies: The research has univariate and bivariate analysis with chi-square test. The research results are 20,9% mothers with non-complete fourth antenatal care, 29,9% mothers with highly pregnant risk, 38,8% mothers with afar residence from integrated health services unit (Posyandu), and 44,8% mother with lower education. Bivariate analysis get no significant correlation between age, distance to Posyandu and the fourth antenatal care, meanwhile it get significant correlation between knowledge and the fourth antenatal care. Intensive Health Education is needed to increase amount of antenatal care, especially the fourth antenatal care.